Investigation of effect of logjam series for varying channel and barrier physical properties using a sparse input data 1D network model. (December 2022) - Follett, Elizabeth; Hankin, Barry
Abstract: Targeted design and placement of natural flood management leaky barriers, or engineered logjams, and accurate representation of logjams in hydraulic models across different scales is necessary to generate desired water storage and flood peak attenuation for effective river restoration and natural flood management projects. We systematically assess the effect of varying logjam spacing, extent of logjam-generated change in water surface profile, vertical height of lower gap, overflow to local floodplain, and varying channel slope, representing a series of logjams in a sparse input data 1D network model including the jam-generated backwater, which depends on loss of momentum within the jam. To guide catchment-scale representation, best-fit increased channel resistance was found to increase with number of jams, approaching an analytically determined maximum for close inter-jam spacing, useful for setting an upper envelope for efficacy. Highlights: A series of logjams was represented by a sparse data input 1D network model. The jam-generated backwater decreased outflow hydrograph skewness for moderate jam spacing. For close jam spacing, effective elevated channel resistance approached an analytical maximum. Presence of a lower vertical gap increased the discharge at which jams overtopped.